Selecting a Structural Analog as an Internal Standard for the Quantification of 6-Methylmercaptopurine by LC-MS/MS. (1st November 2018) - Smith, Kathryn A; Merrigan, Stephen D; Johnson-Davis, Kamisha L
Abstract: Background: When choosing an analog internal standard (IS) in a quantitative LC-MS/MS assay, careful selection and thorough verification are important for developing an accurate quantitative assay. The IS is a critical component in quantitative mass spectrometry because it is used to normalize results by compensating for variations in sample preparation and instrument performance. Here we present the results of our investigation in the selection process for a structural analog IS (SA-IS) to be used in the quantification of 6-methylmercaptopurine (6-MMP) in cytolysed red blood cell (RBC). Methods: A cocktail solution of 9 SA-ISs including the isotopically labeled structural isomer and the 6-MMP stable isotope-labeled IS (SIL-IS) was spiked into cytolysed RBC controls and patient samples. Linearity, accuracy, sensitivity, precision, run stability, method comparison, and reinjection reproducibility experiments were performed. Ion suppression was also assessed by T-infusing the cocktail solution. Results: All analogs were linear from 100 to 1200 ng/mL 6-MMP with acceptable precision and sensitivity by use of a spiked blank lysate. Method comparison plots of 6-MMP concentrations in patient samples had excellent agreement for 2 of the SA-ISs (i.e., the isotopically labeled structural isomer and an SA-IS with an added methyl group) when compared to the SIL-IS. Halogen-substituted analogs (i.e., Cl and Br) also met the criteria as an acceptable IS. However, 2 of the selected SA-ISs having substituted amine moieties showed unacceptable performance, with ≥15% bias when compared to the SIL-IS. Conclusion: There are many parameters to consider when determining if an analog will be a good IS choice, and the approaches highlighted in this article can be applied to the selection of SA-IS in the development of other LC-MS/MS assays.